2015
DOI: 10.1088/0960-1317/25/10/105002
|View full text |Cite
|
Sign up to set email alerts
|

Optical mapping of single-molecule human DNA in disposable, mass-produced all-polymer devices

Abstract: We demonstrate all-polymer injection molded devices for optical mapping of denaturationrenaturation (DR) patterns on long, single DNA-molecules from the human genome. The devices have channels with ultra-low aspect ratio, only 110 nm deep while 20 μm wide, and are superior to the silica devices used previously in the field. With these polymer devices, we demonstrate on-chip recording of DR images of DNA-molecules stretched to more than 95% of their contour length. The stretching is done by opposing flows Marie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(59 reference statements)
0
20
1
Order By: Relevance
“…This is particularly true when the bonding of thermoplastic devices is required on a large scale. Several bonding techniques have been proposed for thermoplastics, the most common being solvent bonding [2], laser welding [3], adhesive bonding [4], and thermal bonding (TB) [5,6]. The bonding step is particularly critical in Lab-on-Chip (LoC) systems with integrated electrodes, the performance of which needs to be maintained while achieving a completely leakage-free system.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true when the bonding of thermoplastic devices is required on a large scale. Several bonding techniques have been proposed for thermoplastics, the most common being solvent bonding [2], laser welding [3], adhesive bonding [4], and thermal bonding (TB) [5,6]. The bonding step is particularly critical in Lab-on-Chip (LoC) systems with integrated electrodes, the performance of which needs to be maintained while achieving a completely leakage-free system.…”
Section: Introductionmentioning
confidence: 99%
“…Novel OM techniques use commercially available reagents in combination with epifluorescence microscopy, standard equipment, and reagents found in many microbiology laboratories. Furthermore, with emerging developments in plastic nanofluidic devices, it has been suggested that the cost per device could be kept as low as $3 (69). The small amount of sample needed for OM is another factor contributing to work-time reduction, as bacterial cultivation steps can potentially be shortened or even omitted.…”
Section: General Considerationsmentioning
confidence: 99%
“…We introduce a novel valve-less microfluidic device for single cell genomics that is manufactured in a thermoplastic material by injection moulding, a process that is scalable at low cost. 23 Our chip design is based on a hydrodynamic cell trap 24 derived from a previously described device for cell culture. 25 Our device design enables the process to be carried out on an optical microscope or in "Cell-O-Matic" a specially built single cell processing instrument (Philips BioCell), in either case allowing us to monitor both cell trapping and genome extraction.…”
Section: Introductionmentioning
confidence: 99%